The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/curroncol28020104
|View full text |Cite
|
Sign up to set email alerts
|

From Theory to Practice: Bone Health in Women with Early Breast Cancer Treated with Aromatase Inhibitors

Abstract: Aromatase inhibitors (AI) are extensively used as adjuvant endocrine therapy in post-menopausal women with hormone receptor-positive early breast cancer (HR+ EBC), but their impact on bone health is not negligible. This work aimed to assess bone loss, fracture incidence, and risk factors associated with these events, as well as the prognostic influence of fractures. We have conducted a retrospective cohort study of women with HR+ EBC under adjuvant therapy with AI, during a 3-year period. Four-hundred-and-fift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…This specific condition is currently defined as cancer treatment-induced bone loss (CTIBL) and might be related to the hormone therapy that negatively affects bone mineral density (BMD) due to the reduction of residual serum endogenous estrogenic levels [5,8,[10][11][12]. Moreover, chemotherapy has been related to an unspecific increase in bone resorption and a higher risk of fragility fractures [13][14][15]. Therefore, specific treatments preventing bone loss and reducing the risk of fragility fractures are strongly recommended to improve the long-term outcomes and management of BC patients [5,16].…”
Section: Introductionmentioning
confidence: 99%
“…This specific condition is currently defined as cancer treatment-induced bone loss (CTIBL) and might be related to the hormone therapy that negatively affects bone mineral density (BMD) due to the reduction of residual serum endogenous estrogenic levels [5,8,[10][11][12]. Moreover, chemotherapy has been related to an unspecific increase in bone resorption and a higher risk of fragility fractures [13][14][15]. Therefore, specific treatments preventing bone loss and reducing the risk of fragility fractures are strongly recommended to improve the long-term outcomes and management of BC patients [5,16].…”
Section: Introductionmentioning
confidence: 99%
“…Leonor et al found that time under AIs is an independent risk factor for joint pain and bone loss, with reduced disease-free survivalin patients. [ 4 ] In the IBIS-II prevention trial, patients who took anastrozole for 5 years had a significant decrease in bone mineral density. [ 5 ] Nearly 10% of breast cancer patients discontinued AIs due to aromatase inhibitor-associated musculoskeletal symptoms (AIMSS).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its benefits in breast cancer treatment, its musculoskeletal impact cannot be ignored. Leonor et al found that time under AIs is an independent risk factor for joint pain and bone loss, with reduced disease-free survivalin patients [4] . In the IBIS-II prevention trial, patients who took anastrozole for 5 years had a significant decrease in bone mineral density [5] .…”
Section: Introductionmentioning
confidence: 99%